2011
DOI: 10.1002/app.33374
|View full text |Cite
|
Sign up to set email alerts
|

Hybridized reinforcement of natural rubber with silane‐modified short cellulose fibers and silica

Abstract: Natural-rubber-based hybrid composites were prepared by the mixture of short cellulose fibers and silica of different relative contents with a 20-phr filler loading with a laboratory two-roll mill. The processability and tensile properties of the hybrid composites were analyzed. The tensile modulus improved, but the tensile strength and elongation at break decreased with increasing cellulose fiber content. The scorch safety improved with the addition of 5-phr cellulose fiber in the composites. The Mooney visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 32 publications
(52 reference statements)
2
28
0
Order By: Relevance
“…Considering the TEM images shown in Figure , the PhOH‐crosslinked NR/clay nanocomposite containing 10 phr clay (PhOH‐NRNC10) showed that the dispersion of clay was relatively poor. It was well accepted that the good dispersion of filler in NR matrix prevented the formation of structural defects, as a result of aggregated filler, which weakened the NR network . Thus, the poor dispersion of clay layer in the NR matrix filled with 10 phr clay caused a decrease of tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the TEM images shown in Figure , the PhOH‐crosslinked NR/clay nanocomposite containing 10 phr clay (PhOH‐NRNC10) showed that the dispersion of clay was relatively poor. It was well accepted that the good dispersion of filler in NR matrix prevented the formation of structural defects, as a result of aggregated filler, which weakened the NR network . Thus, the poor dispersion of clay layer in the NR matrix filled with 10 phr clay caused a decrease of tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…ey suggested that the prolonged scorch time and cure time of NR composites resulted from the better interaction between the filler and rubber matrix. In addition, the increase in scorch time and cure time of NR composites containing TESPT was also reported in natural rubber reinforced with short cellulose fiber/silica [22], natural rubber filled with fly ash [28], and natural rubber reinforced with silica [28].…”
Section: Characterization Of Rhf/nrmentioning
confidence: 96%
“…e small band that occurred at 2931 cm −1 was the stretching vibration of the -CH 2 groups of the attached TESPTon UW-STand W-STsurface [22]. Another absorption band that emerged at 1037 cm −1 was related to the Si-O-Si stretching of the siloxane groups of TESPT on UW-ST and W-STsurface [23].…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…The use of nanofillers to reinforce NR has high expectation because nanofillers have shown in many cases an enhancement of the mechanical properties; conventional inclusion of inorganic fillers by dispersion is more widely used over organic fillers, where carbon black and silica are the most used that have comparable tensile strength, but lower tensile modulus ( E ) than exhibited by silica composites . With the current demand for fillers from renewable resources, organic fillers have become more widely used, especially in the form of fibers, although lower performance than the inorganic fillers has been reported . There are several studies where a synergetic contribution using hybrid fillers (organic–inorganic) appears to enhance mechanical properties as well as increase thermal and physico‐chemical properties …”
Section: Introductionmentioning
confidence: 99%